Response to neoadjuvant chemotherapy and survival of children and adolescents with high-grade osteosarcoma treated based on the EURAMOS-1 protocol - Amaranto Suárez-Mattos; Federico Arroyave; Ana M. Infante; Carlos Narváez; Camilo Soto; Luis Gómez; Javier Amaya-Nieto (Permanyer, 2022)
Background: High-grade osteosarcoma is the most common malignant bone tumor in children and adolescents. This study aimed to evaluate the histologic response to neoadjuvant chemotherapy and overall and event-free survival rates in patients < 21 years of age with a diagnosis of conventional osteosarcoma. Methods: We conducted an analytical and observational study of a cohort of patients < 21 years old with a diagnosis of conventional osteosarcoma treated with the OS INC-2009 protocol (based on EURAMOS-1). Descriptive analysis was performed, and overall and event-free survival rates were calculated by the Kaplan-Meier method. Results: Between April 2009 and October 2016, 84 patients with conventional osteosarcoma (mean age 13.5 ± 3.2 years) were admitted. Metastatic disease at diagnosis was observed in 36 patients (42.8%). Of the 41 patients who received neoadjuvant chemotherapy (50.6%), 15 (36.6%; confidence interval [95%CI]: 49.9-75.6) were classified as good responders and 26 (63%; 95%CI: 22.5-58.0) as poor responders. The 5-year overall and event-free survival rates in good responders were 88.8% (95%CI: 43.3-98.3) and 81.4% (95%CI: 43.5-95.0); in poor responders it was 66.5% (95%CI: 40.7-83.1) and 31.4% (95%CI: 13.8-50.7), respectively. Conclusions: Good responders' evaluation of histologic response to neoadjuvant chemotherapy showed improved overall and event-free survival rates. Specialized centers with multidisciplinary and comprehensive management are required to make the application of high-toxicity protocols feasible.